Effects of vitamin E against aluminum neurotoxicity in rats - Nedzvetsky, VS; Tuzcu, M; Yasar, A; Tikhomirov, AA; Baydas, G (Pleiades Publishing Ltd, 2006)
The present study examined the protective effects of vitamin E against aluminum - induced neurotoxicity in rats. Wistar rats were given daily aluminum via their drinking water containing 1600 mg/liter aluminum chloride for six weeks. Aluminum induced a significant increase in lipid peroxidation (LPO) in hippocampus and frontal cortex. Furthermore, aluminum caused marked elevation in the levels of the glial markers (glial fibrillary acidic protein (GFAP) and S 10013) and proinflammatory cytokines (TNF-alpha and IL-1 beta) in both brain areas. Vitamin E treatment reduced the contents of glial markers and cytokines and the levels of LPO. In conclusion, this study demonstrates that vitamin E ameliorates glial activation and reduces release of proinflammatory cytokines induced by aluminum.
Keywords: aluminum; vitamin E; glial fibrillary acidic protein; S100B protein; lipid peroxidation; glutathione